Answer:
26
Step-by-step explanation:
to get from -6 to a 0, you add 6. 0+20 is 20, so that is how you get it
Answer:
Step-by-step explanation:
x + 3y = 24.....multiply by -1
5x + 3y = 36
------------------
-x - 3y = -24 (result of multiplying by -1)
5x + 3y = 36
------------------add
4x = 12
x = 12/4
x = 3 <=======
x + 3y = 24
3 + 3y = 24
3y = 24 - 3
3y = 21
y = 21/3
y = 7 <========
5x6=30
6x6=36
You would need 1 more 6
I can't explain this very well, sorry.
Answer:
-1, -7, -13, -19
Step-by-step explanation:
-2(-3)-7 =6-7= -1
-2(0)-7 =0-7= -7
-2(3)-7 =-6-7= -13
-2(6)-7 =-12-7= -19
Answer: See below
Step-by-step explanation:
<u>Area of the square</u> = l*w = 11*11 = 121
<u>Area of the circle</u> = pi r^2 = pi*1^2 = 3.142
<u>Part A</u>
P(hitting the circle) = 3.142 / 121 = 0.026 which is closer to 0.
<u>Part B</u>
P(hitting the outside portion) = 1 - 0.026 = 0.974 which is closer to 1.